The Effect of Sponsors Activation on Customer Engagement Behavior in the BRI Super League - Azmiko, Muhammad Luthfi; Astuti, Rifelly Dewi (Dinasti Publisher, 2026)
This study examines the effect of Sponsors Activation on Customer Engagement Disposition (CED) and Customer Engagement Behavior (CEB) within BRI Super League, and investigates the moderating roles of Attitude Toward the Sponsor and Sponsorship Authenticity. A quantitative survey was conducted (n = 214) and analyzed using SEM-PLS with a higher-order construct approach. Results indicate that Sponsors Activation positively and significantly influences CED (β = 0.399; t = 6.680; p < 0.001) and CEB (β = 0.417; t = 8.356; p < 0.001). CED positively influences CEB (β = 0.269; t = 5.909; p < 0.001). Attitude Toward the Sponsor moderates the Sponsors Activation–CED relationship (β = 0.269; t = 5.679), while Sponsorship Authenticity moderates both the Sponsors Activation–CED (β = 0.340) and Sponsors Activation–CEB (β = 0.432) relationships. CEB is confirmed as a second-order reflective construct reflected by augmenting, co-developing, influencing, and mobilizing behavior. This research contributes to sport sponsorship and customer engagement literature by elucidating the mechanism through which sponsorship activation generates meaningful and sustainable customer engagement.